Pneumocystosis in dogs: meta-analysis of 43 published cases including clinical signs, diagnostic procedures, and treatment. (January 2018) - Weissenbacher-Lang, Christiane; Fuchs-Baumgartinger, Andrea; Guija-De-Arespacochaga, Abigail; Klang, Andrea; Weissenböck, Herbert; Künzel, Frank
We evaluated 43 published cases of dogs with confirmed Pneumocystis infection regarding the value of clinical parameters indicating the presence of the disease as well as tools for the detection of the pathogen. The assessed parameters included clinical signs, laboratory findings, results of thoracic radiography, autopsy, histopathology, methods for the detection of Pneumocystis, as well as medical therapy. Pneumocystosis was diagnosed most often in certain breeds (Cavalier King Charles Spaniel, Miniature Dachshund) with a predisposition for impaired immunity. The median age of the dogs was 1 y. Chronic therapy-resistant respiratory signs, such as tachypnea, dyspnea, and cough, along with leukocytosis, neutrophilia, and hypogammaglobulinemia, were the most frequently described clinical and clinicopathologic abnormalities. Pneumocystosis can be masked by coinfections with other respiratory pathogens, and the successful detection of Pneumocystis organisms is of major relevance. Several detection methods have been used in the past, but only a few provide reliable results. In 2017, the cytologic evaluation of Giemsa-stained bronchoalveolar lavage samples is generally used, even if sensitivity is only moderate. More reliable results can be achieved using special stains or sensitive molecular techniques. Fast and reliable detection of Pneumocystis is the essential basis for appropriate treatment and higher survival chances for dogs.